Electron dynamics and metastable species generation in atmospheric pressure non-equilibrium plasmas controlled by dual LF–RF frequency discharges - Yu, Yilin; Zhang, Zhonglin; Nie, Qiuyue; Zeng, Jiacheng; Zhao, Zhibo; Wang, Xiaogang (Frontiers in Physics, 2023)
In this work, we report an approach to control electron dynamics and metastable species generation and enhance the density of atmospheric pressure non-equilibrium plasmas by using dual-frequency excitation sources. The atmospheric dielectric barrier discharge of an α-mode radio frequency (RF=5 MHz) discharge controlled by a low frequency (LF=50 kHz) bias is studied based on a one-dimensional (1D) fluid model. Results show that the variation of applied voltages of RF and LF is able to modulate the electron dynamic process, resulting in different spatial distributions of electron and metastable particle densities. Moreover, it is further shown that the electron density has a substantially increase when the LF component voltage amplitude is larger than 300 V for the initial setting. The discharge process is characterized by fast Fourier transform of the spatio-temporal evolution of the electron power absorption and discharge current. As the LF be applied, three wave interactions induced by LF and RF coupling can be clearly observed, with the sum- and beat -frequencies between LF and RF are raised, which results in a substantial increase of the electron density. On the other hand, the high RF harmonics, especially for the fundamental and the third harmonic components, are suppressed with increasing the LF component. This work exhibits dual-frequency excitation for its capacity to modulate the electron dynamic behavior and metastable species generation at atmospheric pressure plasma, which can provide a possible approach of optimizing plasma parameters.